Kesiapan Implementasi SAK EMKM Pada UMKM Di Jepara (Studi Kasus di UMKM Safila Collection dan Fizaria Hijab) - Aliyah, Siti; Safitri, Difi; Subadriyah, Subadriyah (Accounting Study Program, Faculty of Economics and Business, 2023)
This study aims to find out how far MSME actors are in implementing the preparation of financial statements based on Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). Researchers also want to know the factors that cause SAK EMKM-based financial statements not being prepared for MSME. This study uses a descriptive qualitative data analysis method. The data in this study were obtained from secondary data and primary data. Data collection techniques using the triangulation method (interviews and documentation). The results of the research and discussion that have been presented can be concluded that the Safila Collection UMKM have not prepared SAK EMKM-based financial statements at all which can be proven by not finding the preparation of balance sheets, profit and loss reports, and notes to financial statements. Whereas the Fizaria Hijab MSMEs have implemented SAK EMKM-based financial reports as evidenced by the preparation of balance sheets, profit and loss reports, and reports on changes in capital, but have not compiled notes on the financial statements in their business.